A decrease in the incidence of encephalitis in South Korea during the COVID‐19 pandemic: A nationwide study between 2010 and 2021. Issue 2 (20th January 2023) - Kim, Se Hee; Baek, Jee Yeon; Han, Minkyung; Lee, Myeongjee; Lim, Sung Min; Lee, Ji Young; Kang, Ji‐Man; Jung, Inkyung; Kang, Hoon‐Chul; Ahn, Jong Gyun
Abstract: Limited data are available on the impact of the coronavirus disease (COVID‐19) pandemic on encephalitis. Therefore, we evaluated trends in encephalitis in South Korea between 2010 and 2021 using data from the National Health Insurance Service. During the pandemic (February 2020 to 2021), the monthly incidence of encephalitis declined by 0.027 per 100 000 population (95% confidence interval [CI]: −0.055 to 0.001, p  = 0.062) compared to that before the pandemic. In subgroup analysis, the estimated coefficient for level change during the pandemic in the 0–4 and 5–9 years age groups were −2.050 (95% CI: −2.972 to −1.128, p  < 0.001) and −0.813 (95% CI: −1.399 to −0.227, p  = 0.008), respectively. The annual incidence of encephalitis during the pandemic period significantly decreased in the 0–4 and 5–9 years age groups (incidence rate ratio: 0.34 [ p  = 0.007] and 0.28 [ p  = 0.024], respectively). The intensive care unit admission rate (39.1% vs. 58.9%, p  < 0.001) and cases of death (8.9% vs. 11.1%, p  < 0.001) decreased significantly during the pandemic compared to the prepandemic. During the pandemic, the incidence of encephalitis decreased markedly in South Korea, particularly in children aged ≤9 years. In addition, there were changes in the clinical outcome of encephalitis during the COVID‐19 pandemic.